1999
DOI: 10.1002/(sici)1097-4644(19991201)75:3<528::aid-jcb16>3.3.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol formation by human osteoblasts via multiple pathways: Relation with osteoblast function

Abstract: The importance of estrogens in bone metabolism is illustrated by the accelerated bone loss and increase in osteoporotic fractures associated with postmenopausal estrogen deficiency. In this study, the expression and activity of the enzymes involved in estrogen metabolism in human osteoblastic cells were investigated in relation to differentiation of these cells. PCR reactions using mRNA from an in vitro differentiating human cell line (SV-HFO) were performed to assess mRNA expression of the enzymes aromatase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 0 publications
1
43
0
3
Order By: Relevance
“…In addition to gonads, this enzyme is found in different organs, including adipose tissue, brain, skin, endothelium and bone. Skeletal cells also express a number of other enzymes implicated in sex steroid metabolism (Schweikert et al 1980, Janssen et al 1999, Compston 2002, Ishida et al 2002, Issa et al 2002, supporting the concept that active androgens and oestrogens can be synthesized within the bone marrow cells from circulating C19 precursors. Thus, besides contributing to the circulating oestrogen pool, the oestrogen synthesized within bone tissue compartments may be locally active in a paracrine or intracrine way (Labrie et al 1997, Simpson 2000, Simpson & Davis 2001.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…In addition to gonads, this enzyme is found in different organs, including adipose tissue, brain, skin, endothelium and bone. Skeletal cells also express a number of other enzymes implicated in sex steroid metabolism (Schweikert et al 1980, Janssen et al 1999, Compston 2002, Ishida et al 2002, Issa et al 2002, supporting the concept that active androgens and oestrogens can be synthesized within the bone marrow cells from circulating C19 precursors. Thus, besides contributing to the circulating oestrogen pool, the oestrogen synthesized within bone tissue compartments may be locally active in a paracrine or intracrine way (Labrie et al 1997, Simpson 2000, Simpson & Davis 2001.…”
Section: Introductionmentioning
confidence: 87%
“…Aromatase has been reported to be expressed in hMSCs (Heim et al 2004), in osteoblast or osteoblast-like cells from foetal and adult tissues (Purohit et al 1992, Tanaka et al 1993, Schweikert et al 1995, Sasano et al 1997, Janssen et al 1999, in articular cartilage chondrocytes, in adipocytes adjacent to bone trabeculae, in osteocytes (Sasano et al 1997) and in macrophage/osteoclast-like cells (Shozu et al 1997). The expression of CYP 19 has been shown to be regulated by differential promoter usage, depending on the tissue context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SV-HFO cell line was established from human fetal calvaria, and retains the features of human osteoblasts well (13). Aromatase activity and gene transcript were detected in SV-HFO (14). Aromatase activity and CYP19 gene transcript were up-regulated in a Dex-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatase activity has been detected in several human adult and fetal tissues, and pathologic samples (9,10). With regard to bone, aromatase activity and/or aromatase mRNA have been detected in tissue samples (11 -13), in human cultured osteoblasts (14,15), in human osteosarcoma cell lines HOS, U2OS and MG63 (4 -6, 14, 16), in differentiating human osteoblastic cells such as SV-HFO (17), and in SV40-immortalized human osteoblasts (5,6). A fairly recent study (15) has shown that promoter usage and regulation of aromatase gene expression in osteoblast-like cells may be specific and different from those of other tissues such as placenta, ovary and adipose tissue.…”
Section: Introductionmentioning
confidence: 99%